TANTANGAN DAN PELUANG DALAM PENERAPAN AKUNTANSI MANAJEMEN BERKELANJUTAN DI NEGARA BERKEMBANG - Firdaus; Dwi Astono, Ari; Nurhayati, Nurhayati; Jatmiko, M Roby; Sitti Nurrahmah, Wa Ode; Sulistiyaningsih, Sri; Hendriyanto, Asepta; Mulyanto, Kukuh; Ismanto, Fiderius; Effendi, Meizar (LPPM Universitas Sains Dan Teknologi Komputer, 2024)
The implementation of Sustainable Management Accounting (SMA) in developing nations is examined in this paper along with its prospects and obstacles. To achieve long-term sustainability, SMA incorporates social, economic, and environmental factors into business decision-making. SMA adoption in underdeveloped nations is hampered by issues like a lack of funding, a lack of environmental consciousness, and a lack of training and technology. SMA does, however, also have a number of noteworthy advantages, including increased operational effectiveness, better risk management, and higher standing in a global marketplace that is becoming more and more concerned with sustainability. This study examines the challenges and tactics in implementing SMA using a qualitative methodology and case studies of businesses in underdeveloped nations. It is anticipated that the results will help businesses and policymakers create and implement SMA in a way that promotes social, economic, and environmental sustainability.